A Cooperative Strategy for the Highly Selective Intermolecular Oxycarbonylation Reaction of Alkenes using a Palladium Catalyst. (6th October 2016) - Li, Ming; Yu, Feng; Qi, Xiaoxu; Chen, Pinhong; Liu, Guosheng
Abstract: A novel method for intermolecular functionalization of terminal and internal alkenes has been designed. The electrophilic reagent, hypervalent iodine, plays a key role in this process by activating the alkene C=C bond for nucleophilic addition of the palladium catalyst. This process generates an iodonium‐containing palladium species which undergoes CO insertion. The new approach, intermolecular oxycarbonylaton reactions of alkenes, has been achieved and carried out under mild reaction conditions to produce the corresponding β‐oxycarbonylic acids with excellent efficiencies and levels of regio‐ and diastereoselectivity.